1998
DOI: 10.1002/lt.500040107
|View full text |Cite
|
Sign up to set email alerts
|

The significance of aerobic gram-negative bacilli in clinical specimens following orthotopic liver transplantation

Abstract: In a prospective study of 284 liver transplant patients, we sought associations between aerobic gram-negative bacillus acquisition or infection and 35 preoperative, perioperative, and postoperative variables. Although the 128 (45%) who acquired aerobic gram-negative bacilli had longer admissions (P ‫؍‬ 0.0001), no associations were found with pretransplant variables. Fifty-three (41%) of the 128 acquired coliforms (e.g., Escherichia coli, Klebsiella spp., or Enterobacter spp.), 50 (39%) acquired nonfermentativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…These results are concordant with a previous report studying the significance of aerobic Gram‐negative bacilli in clinical specimens after OLT [30]. Among 284 patients undergoing OLT, only nine (3%) demonstrated a positive bile culture growing an Enterobacteriaceae species.…”
Section: Discussionsupporting
confidence: 92%
“…These results are concordant with a previous report studying the significance of aerobic Gram‐negative bacilli in clinical specimens after OLT [30]. Among 284 patients undergoing OLT, only nine (3%) demonstrated a positive bile culture growing an Enterobacteriaceae species.…”
Section: Discussionsupporting
confidence: 92%
“…Preoperative infections are significant sources of morbidity, mortality, and resource utilization among orthotopic liver transplant recipients. 5,6,[29][30][31] In this study of 777 first, single organ transplant recipients from the NIDDK Liver Transplantation Database, we found that transplant recipients who develop surgical site infections had a significantly higher rate of graft loss, accumulated more than 24 additional hospital days, and incurred approximately $131,000 in excess charges. As noted previously, these excess charges represent 1995 dollars.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, infectious complications remain a substantial problem after OLT. [5][6][7] Liver transplant recipients are particularly susceptible to infection. The surgical procedure itself is complex and can take many hours, even in the best of hands, and has the potential for contamination via the gastrointestinal tract.…”
mentioning
confidence: 99%
“…2 It is associated with signifi cant morbidity and mortality rates because it shows a resistance to almost all the currently available antibiotics.…”
Section: Introductionmentioning
confidence: 99%